For \( f(x)=x^{2}+2 \) and \( g(x)=\sqrt{4-x} \), find a. ( \( f \circ g)(x) \); b. the domain of \( f \circ g \) a. ( \( f \circ g)(x)=6-x \) (Simplify your answer.) b. What is the domain of \( f \circ g ? \) ? The domain is (Simplify your answer. Type your answer in interval notation. Use integers the expression.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To find \( (f \circ g)(x) = f(g(x)) \), we start by substituting \( g(x) \) into \( f(x) \). 1. First, compute \( g(x) = \sqrt{4 - x} \). 2. Now substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(\sqrt{4 - x}) = (\sqrt{4 - x})^2 + 2 = (4 - x) + 2 = 6 - x. \] So, \( (f \circ g)(x) = 6 - x \). To determine the domain of \( f \circ g \): 1. The function \( g(x) = \sqrt{4 - x} \) is defined when \( 4 - x \geq 0 \), which simplifies to \( x \leq 4 \). 2. Since \( g(x) \) outputs values for \( x \leq 4 \), and there are no additional constraints from \( f(x) \), the domain of \( f \circ g \) is determined solely by \( g(x) \). Thus, the domain of \( f \circ g \) is \( (-\infty, 4] \).